Force-limiting and the mechanical response of natural turfgrass used in the National Football League: A step toward the elimination of differential lower limb injury risk on synthetic turf - Kent, R.; Yoder, J.; O'Cain, C. M.; Spratley, E. M.; Arbogast, K. B.; Sorochan, J.; McNitt, A.; Serensits, T. (Journal of Biomechanics, 2021)
Lower limb injury rate in the National Football League (NFL) is greater on synthetic turf than on natural turfgrass. Foot loading in potentially injurious situations can be mitigated by damage to natural turfgrass that limits the peak load by allowing relative motion between the foot and the ground. Synthetic turf surfaces do not typically sustain such damage and thus lack such a load-limiting mechanism. To guide innovation in synthetic turf design, this paper reports 1) the peak loads of natural turfgrass when loaded by a cleated footform and 2) corridors that define the load-displacement response. Kentucky bluegrass [Poa pratensis, L.] and two cultivars of hybrid bermudagrass [Cynodon dactylon (L.) Pers × C. transvaalensis Burtt Davy] were tested with two cleat patterns in three loading modes (anterior-posterior or AP translation, medial-lateral or ML translation, and forefoot external rotation) at two power levels (full-power, which generated potentially injurious loads, and reduced-power, which generated horizontal forces similar to non-injurious ground reaction forces applied by an elite athlete during play). All tests generated peak force<4.95 kN and torque<173 Nm, which is in a loading regime that would be expected to mitigate injury risk. In full-power tests, bermudagrass withstood significantly (p < 0.05) greater peak loads than Kentucky bluegrass: (3.86 ± 0.45 kN vs. 2.66 ± 0.23 kN in AP, 3.25 ± 0.45 kN vs. 2.49 ± 0.36 kN in ML, and 144.8 ± 12.0 Nm vs. 126.3 ± 6.1 Nm in rotation). Corridors are reported that describe the load-displacement response aggregated across all surfaces tested.